The gut microbiota in Graves’ disease: mechanistic insights and clinical implications - Leyang Li; Boxian Pang; Ze Wang; Di Zhao; Junping Wei; Qiuhong Wang (Frontiers in Cellular and Infection Microbiology, 2026)
Graves’ disease (GD) is an autoimmune form of hyperthyroidism characterized by loss of immune tolerance to the thyrotropin receptor and sustained thyroid hormone excess. Interest in the gut–thyroid axis has expanded rapidly, placing the gut microbiota within current models of GD pathophysiology. This review summarizes current evidence on gut microbial alterations in GD and discusses how these changes may intersect with thyroid autoimmunity. Available studies broadly support disruption of the intestinal microbial ecosystem in GD, although findings for individual taxa and diversity indices vary across cohorts. Proposed links between dysbiosis and disease include altered short-chain fatty acid and bile acid metabolism, impairment of epithelial barrier integrity with translocation of microbial products, shifts in Th17/Treg balance and related immune activation, molecular mimicry, and disturbed handling of micronutrients involved in thyroid hormone synthesis and metabolism. The oral–gut microbial connection has also emerged as a potentially relevant dimension of disease-associated dysbiosis. In parallel, microbiota-directed approaches, including probiotics, prebiotics, synbiotics, dietary modulation, and fecal microbiota transplantation, are being explored as possible adjuncts in GD management. Overall, gut microbial disturbance offers a biologically plausible link between environmental exposure, immune disequilibrium, and thyroid dysfunction in GD; however, stronger mechanistic, longitudinal, and interventional evidence is still required before these findings can be translated into precision clinical practice.